1995
DOI: 10.1139/v95-121
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of heptamethylindenyl rhodium(III) complexes: molecular structures of [(η5-C9Me7)RhCl(µ-Cl)]2 and [(η5-C9Me7)Rh(PMe2Ph)Cl2]

Abstract: Key words: rhodium, indenyl, permethylindenyl, heptamethylindenyl, phosphine complex, X-ray structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…In contrast with the parent indenyl ligand (Ind), Ind* is known to adopt an η 5 coordination mode on the Rhodium metal in the ground state such as Cp* with little to no tilting of the ligand toward η 3 . 31 We observed that variation at the para and meta positions of the cyclopropene units furnish the product in good yields and excellent diastereoselectivities, regardless of the electronic nature of the substituents. The observed major diastereoisomer can be rationalized through the size of the substituents on the cyclopropane ring.…”
Section: ■ Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…In contrast with the parent indenyl ligand (Ind), Ind* is known to adopt an η 5 coordination mode on the Rhodium metal in the ground state such as Cp* with little to no tilting of the ligand toward η 3 . 31 We observed that variation at the para and meta positions of the cyclopropene units furnish the product in good yields and excellent diastereoselectivities, regardless of the electronic nature of the substituents. The observed major diastereoisomer can be rationalized through the size of the substituents on the cyclopropane ring.…”
Section: ■ Introductionmentioning
confidence: 70%
“…While Cp t and Cp* CF3 ligands deliver promising diastereoselectivity, heptamethylindenyl ligand (Ind*) proves to be the ligand of choice providing the bicyclic product in 90% yield and 15.2:1 dr. In contrast with the parent indenyl ligand (Ind), Ind* is known to adopt an η 5 coordination mode on the Rhodium metal in the ground state such as Cp* with little to no tilting of the ligand towards η 3 31 . We observed that variation at the para and meta positions of the cyclopropene units furnish the product in good yields and excellent diastereoselectivities, regardless of the electronic nature of the substituents.…”
Section: Synthesis Of Isoquinolones Pyridones and Their Derivativesmentioning
confidence: 99%
“…Good level of diastereocontrol (8.8 : 1 dr) is achieved when tert -butyl tetramethylcyclopentadienyl 12 (Cp* t Bu ) ligand was employed (entry 6). Gratifyingly, heptamethylindenyl ligand 14 (Ind*) provides high reactivity and diastereoselectivity with 90% yield and 15.2 : 1 dr (entry 7). To demonstrate the scalability of the transformation, the reaction was performed in 2 mmol scale of substrate 1a , which gives the expected product with comparable yield and selectivity.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of the methoxy group or the 2-methyl group further decreasedt he D value (5ba vs. 5bb and 5da), which were close to the D value of the highly stable Ind* complex. [13,14] This feature predicts high stability of the indenyl complexes derived from 3bb and 3da.…”
mentioning
confidence: 99%
“…[b] Ref. [13]. ducted under air.A tt he initial stage (1-2 h), the use of 4da produced 9aa in higher yield than that of 6ba and the Cp E Rh III complex.F urthermore, the reactionu sing 4da continuously generated 9aa even at the late stage (2-18 h).…”
mentioning
confidence: 99%